ANALYSIS OF FACTORS INFLUENCING CONSUMER DECISIONS IN BUYING COOKING OIL IN GALANG CITY, DELI SERDANG REGENCY, NORTH SUMATERA - Rica Jaisika; Damayanti; Adhiana; Suryadi (Universitas Efarina, 2023)
Galang City is a trading center in Galang sub-district which has experienced an increase in cooking oil prices, cooking oil shortages and panic buying cooking oil since October 2021. This condition makes the people of Galang City reconsider buying the type of cooking oil that they will consume, who originally bought packaged cooking oil now switch to buy bulk cooking oil. The research aims to analyze the factors influencing customer decisions and analyze customer opportunities for bulk and packaged cooking oil in Galang City, Deli Serdang district, North Sumatra. This research is located in Galang City and will be carried out from January to February 2023. Sampling was carried out using the accidental sampling method and number of samples was determined using the Slovin formula technique with a sample result of 96 respondents. The analytical method used in this research is the binary logistic analysis method which will be processed using Microsoft Excel and SPSS16. The result of this research is that the variable price of cooking oil has a significant effect on customer decisions in purchasing cooking oil. While the variables age, education, income, and number of family members do not have a significant effect on consumer decisions in purchasing cooking oil. In addition, the variables age, education, income, and number of family members are positive coefficients. While the price of cooking oil is worth a negative coefficient.